Differences in background characteristics of patients with chronic hepatitis C who achieved sustained virologic response with interferon‐free versus interferon‐based therapy and the risk of developing hepatocellular carcinoma after eradication of hepatitis C virus in Japan. Issue 6 (11th January 2017) - Toyoda, H.; Tada, T.; Takaguchi, K.; Senoh, T.; Shimada, N.; Hiraoka, A.; Michitaka, K.; Ishikawa, T.; Kumada, T.
Summary: We compared the background characteristics of patients with chronic hepatitis C who achieved eradication of hepatitis C virus (HCV), that is sustained virologic response (SVR), with interferon (IFN)‐based versus IFN‐free antiviral therapy in Japan. In addition, we used a previously reported risk assessment model to compare the incidence of hepatocellular carcinoma (HCC) after SVR by treatment type. Pretreatment characteristics of 1533 patients who achieved SVR with IFN‐based therapy and 1086 patients with IFN‐free therapy from five institutions across Japan were compared. The risk of HCC after SVR was assessed based on pretreatment characteristics, and the incidence of HCC after SVR was estimated in both groups. Age and serum alpha‐fetoprotein levels were higher, platelet count was lower, and liver fibrosis was more advanced in patients who achieved SVR with IFN‐free therapy compared with IFN‐based therapy. The incidence of HCC after SVR in the IFN‐free group was estimated to be more than twofold higher than in the IFN‐based therapy group (7.29% vs. 3.09%, and 6.23% vs. 3.01% when excluding patients who have underwent curative treatment for HCC). There are large differences in pretreatment characteristics between patients who achieved SVR with IFN‐based and IFN‐free therapies in Japan, which are associated with differential risk of HCC after SVR. These differences can influence the incidence of HCC after SVR and should be taken into consideration when comparing IFN‐based and IFN‐free therapies in terms of hepatocarcinogenesis suppression with HCV eradication.